Visualizing Post‐Translational Modifications in Protein Interaction Networks Using PTMOracle. Issue 1 (17th January 2019) - Tay, Aidan P.; Liang, Angelita; Wilkins, Marc R.; Pang, Chi Nam Ignatius
Abstract: Post‐translational modifications (PTMs) of proteins act as key regulators of protein activity, including the regulation of protein‐protein interactions (PPIs). However, exploring functional links between PTMs and PPIs can be difficult. PTMOracle is a Cytoscape app that facilitates the co‐visualization and co‐analysis of PTMs in the context of PPI networks. PTMOracle also allows extensive data to be integrated and co‐analyzed, allowing the role of domains, motifs, and disordered regions to be considered. Here, we describe several PTMOracle protocols investigating complex PTM‐associated relationships and their role in PPIs. This is assisted by OraclePainter for coloring proteins by the modifications present and visualizing these in the context of networks, by OracleTools for cross‐matching PTMs with sequence feature for all nodes in the network, and by OracleResults for exploring specific proteins and visualizing their PTMs in the context of protein sequences. This unit aims to demonstrate how PTMOracle can be used to systematically explore network visualizations and generate testable hypotheses regarding the functional role of PTMs in PPIs, and how the results can be analyzed to better understand the regulatory role of PTMs in PPIs. © 2019 by John Wiley & Sons, Inc.